1999
DOI: 10.1073/pnas.96.23.13456
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exposure to high corticosterone levels attenuates serotonin responses in rat hippocampal CA1 neurons

Abstract: Recent studies indicated that hyperactivity of the hypothalamopituitary-adrenal system is a considerable risk factor for the precipitation of affective disorders, most notably of major depression. The mechanism by which this hyperactivity eventually leads to clinical symptoms of depression is unknown. In the present animal study, we tested one possible mechanism, i.e., that long-term exposure to high corticosterone levels alters functional responses to serotonin in the hippocampus, an important area in the eti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
72
4
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 44 publications
(61 reference statements)
13
72
4
4
Order By: Relevance
“…This differs from what is found with exogenous administration of very high doses of corticosterone (eg, Karten et al, 1999) and may indicate that the increase in corticosteroid level after chronic unpredictable stress is relatively mild. Interestingly, the change in bodyweight gain after chronic stress was not normalized by RU 38486 treatment.…”
Section: Chronic Stress Protocolcontrasting
confidence: 74%
“…This differs from what is found with exogenous administration of very high doses of corticosterone (eg, Karten et al, 1999) and may indicate that the increase in corticosteroid level after chronic unpredictable stress is relatively mild. Interestingly, the change in bodyweight gain after chronic stress was not normalized by RU 38486 treatment.…”
Section: Chronic Stress Protocolcontrasting
confidence: 74%
“…Specifically, the MR system seems to control the sensitivity of the CRH-1 system (de Kloet, 2003), which is thought to be altered in MDD, and to be the primary mediator of 5-HT 1A downregulation after chronic stress (Kuroda et al, 1994), whereas the GR seems to be the primary receptor involved in stress-related 5-HT 2A receptor upregulation (Karten et al, 1999).…”
Section: Hpa Axis and Crhmentioning
confidence: 99%
“…Recent evidence has suggested that 5-HT 1A receptor sensitivity in the dorsal raphe nucleus and the hippocampus may be altered by prolonged glucocorticoid administration (Fairchild, Leitch, & Ingram, 2003;Karten, Nair, van Essen, Sibug, & Joëls, 1999), and this may have consequences for 5-HT neurotransmission in key projection regions such as the frontal cortex (Gartside, Leitch, & Young, 2003;see Porter, Gallagher, Watson, & Young, 2004, for a review of the evidence for effects of glucocorticoids on 5-HT function in humans).…”
Section: Interactions Between the 5-ht System And The Hpa Axismentioning
confidence: 99%